Sociological Ambivalence in Reproduction: Natural Childbirth and Technological Conception - Bandelli, Daniela (Italian Sociological Review, 2024)
Procreative choices and discourses in contemporary society are steered by the insistence on nature and the trust in biomedical technologies. Whilst biomedical technologies are increasingly used in conception, the critique of medicalisation in childbirth is a matter of collective sensitivity. Through the theory of sociological ambivalence, this study sheds lights on the strategies adopted by childbirth professionals to cope with the nature/technique polarity. Results of a qualitative study conducted with midwives, doulas and trainers in Italy are presentede.